Hydrological Modeling for Multifunctional Landscape Planning in the Orinoquia Region of Colombia - Pimentel, Jonathan Nogales; Rogéliz Prada, Carlos Andres; Walschburger, Thomas (Frontiers in Environmental Science, 2021)
With over 200,000 km2 of natural savannas, the Orinoquia region of Colombia is a key and strategic conservation area. Because of Colombia’s fast economic growth, there are significant plans for agro-industrial expansion in the Orinoquia. This expansion may seriously affect water availability. To evaluate the cumulative impacts on freshwater ecosystems derived by different expansion scenarios, the use of a comprehensive framework for mathematical modeling, able to represent the hydrological processes at a macro-basin scale, is crucial for analysis and as a tool to bridge the gap between science and practice. In this work, we developed a general methodological framework for hydrological analysis at macro-basin scale consisting of four main stages: 1) collection and processing of hydro climatological data, 2) characterization of hydro dependent water use sectors, 3) mathematical modeling and 4) scenario simulation. As a result of applying the proposed framework, we obtained a coupled hydrological model, which allows us to represent the rain-runoff process, the river-floodplain interaction and anthropic processes such as surface water extraction and groundwater extraction, enabling us to represent the complexity of the Orinoquia region. The model was successfully implemented in Matlab showing a Nash-Sutcliffe efficiency coefficient between 0.62 and 0.92 in calibration and between 0.49 and 0.92 in validation. With this model we analyzed five different agro-industrial expansion scenarios, finding that the Colombian Orinoquia may have future high pressure on water resource areas with critical changes in the water availability regime. The scenarios show reductions of up to 85% in low water flows in more than 50% of the area of the Colombian Orinoco basin. In the most extreme scenarios, the Meta, Vichada and Guaviare rivers show reductions of 95%, 98% and 50% in low water flows. The results show an urgent need to consider hydrology in planning processes to ensure the sustainability of this important area in Colombia.